Територіальні особливості водно-ресурсного потенціалу Харківської області - Клименко, В.Г.; Klimenko, V.G. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
Комплексне оцінювання і детальна характеристика водно-ресурсного потенціалу Харківської області з метою раціонального водокористування і водоспоживання в регіоні. Complex assessment and detailed characteristics of water and resource potential of Kharkov region with the aim of rational water use and water consumption in the region.
Territorial features of water-resource potential of the Kharkov region
Keywords: водні ресурси; регіональний фактор розвитку; раціональне водокористування; водные ресурсы; региональный фактор развития; рациональное природопользование; water resources; regional factor of development; rational wildlife management